Experience of September 12 coup d'etat in Turkish novels of the 1980s - Özdoğan, Başak Deniz. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2008., 2008)
This study scrutinizes the September 12 literature written just after the September 12 coup d’état, that is to say in 1980s. How the coup affected to the literature both its form and content; how the coup experienced by the authors and how the coup is represented within the novels in 1980s are the basic questions of this study. For this purpose, this study examines the September 12 novels, including to its field both the works of the canonized authors and the prison literature. Main focus of this study is the prison literature of 1980s which is considered as both a resistance space and as a representative of the hegemonic mentality of the period. It is suggested that the exclusion of the prison literature from the literary history is the representation of the exclusion of the prisoners from the politics and the public sphere. This study examines both the canonized literature of September 12 and the prison literature to analyze the entire atmosphere of the 1980s which was shaped by the military take over.
Keywords: Turkish literature -- 20th century -- History and criticism.; Politics and literature.